SUMITRO HADI: SENIMAN TARI DI BANYUWANGI TAHUN 1968 - 2020 - Sa'adah, Ririn Wahidatus; IG Krisnadi; Sasmita, Nurhadi (Historia, 2025)
This study is a biographical study that discusses the life of Sumitro Hadi, a dance artist in Banyuwangi from 1968 to 2020. The research questions in this study are: (1) What was the background of Sumitro Hadi becoming a dance artist in Banyuwangi? (2) How did Sumitro Hadi's creativity develop as a dance artist in Banyuwangi? (3) How did Sumitro Hadi influence the socio-culture and the final period of his becoming a dance artist in Banyuwangi. The method used in this writing is the historical method which consists of 5 stages, namely topic selection, heuristics, criticism, interpretation and historiography. The results of this study are (1) a complete biography of Sumitro Hadi's life as a dance artist in Banyuwangi which was formed from the habitus of the family environment, educational environment and community environment. (2) Sumitro Hadi's creativity in developing dance arts through education and attracting the interest of the younger generation to preserve Banyuwangi dance arts as well as the cultural achievements obtained by Sumitro Hadi as a Banyuwangi dance artist who can deliver Banyuwangi arts both in the National and International arenas (3) new dance studios began to emerge when Sumitro Hadi's Sanggar Jingga Putih was no longer active and most of the studio owners were Sumitro Hadi's students who had studied at Sanggar Jingga Putih. Sumitro Hadi's final journey as a dance artist who was creative in dance arts ended in 2020 because Sumitro Hadi died on December 26, 2020 due to Corona Virus Disease (Covid-19).